An evaluation of motor evoked potential surrogate endpoints during intracranial vascular procedures. Issue 2 (February 2016) - Holdefer, R.N.; MacDonald, D.B.; Guo, L.; Skinner, S.A.
Highlights: Motor evoked potentials (MEPs) during intracranial vascular surgeries are used as surrogate endpoints to predict the efficacy of interventions to avoid new postoperative deficits. The probability of a new postoperative deficit was reduced by 60% for reversible, as compared to irreversible, MEP deteriorations in a meta-analysis of recent studies. The efficacy of interventions in recovering MEP deteriorations was negatively correlated with new postoperative deficits in motor strength. Abstract: Objective: MEPs are used as surrogate endpoints to predict the effectiveness of interventions, made in response to MEP deterioration, in avoiding new postoperative deficits. MEP performance in capturing intervention effects on these outcomes was investigated. Methods: A meta-analysis of studies using MEPs during intracranial vascular surgeries between 2003 and 2014 was performed. MEP diagnostic performance and relative risk of new postoperative deficits for reversible compared with irreversible MEP changes were determined. Intervention efficacy in reversing MEP deterioration and postoperative outcomes was compared across studies. Results: MEP diagnostic performance compared favorably with that of other tests used in medicine, with all likelihood ratios >10. The summary relative risk comparing reversible and irreversible changes was 0.40, indicating a 60% decrease in new deficits for reversible MEP changes. The proportion of MEP deteriorations which recovered was negatively correlated with the proportion of new postoperative deficits ( r = −0.81, p < .005). Conclusions: The effectiveness of interventions in recovering an MEP decline was predictive of preserved neurologic status. MEPs are provisionally qualified as surrogate endpoints given potentially major harms to the patient if they are not used, compared to the minimal harms and costs associated with their use. Significance: The performance of MEPs as substitute, or surrogate, endpoints during intracranial vascular surgeries for new deficits in motor strength in the immediate postoperative period was directly assessed for ten recent studies.